Multi-service prevention programs for pregnant and parenting women with substance use and multiple vulnerabilities: Program structure and clients' perspectives on wraparound programming - Deborah Rutman; Carol Hubberstey; Nancy Poole; Rose A. Schmidt; Marilyn Van Bibber (BMC, 2020)
Abstract Background In Canada, several community-based, multi-service programs aimed at reaching vulnerable pregnant or parenting women with substance use and complex issues have emerged. These programs offer basic needs and social supports along with perinatal, primary, and mental health care, as well as substance use services. Evaluations of these 'one-stop' programs have demonstrated positive outcomes; nevertheless, few published studies have focused on how these programs are structured, on their cross-sectoral partnerships, and on clients' perceptions of their services. Methods The Co-Creating Evidence (CCE) project was a three-year evaluation of eight multi-service programs located in six Canadian jurisdictions. The study used a mixed-methods design involving semi-structured interviews, questionnaires, output data, and de-identified client data. This article focuses on qualitative interviews undertaken with 125 clients during the first round of site visits, supplemented by interview data with program staff and service partners. Results Each of the programs in the CCE study employs a multi-service model that both reflects a wrap-around approach to care and is intentionally geared to removing barriers to accessing services. The programs are either operated by a health authority (n = 4) or by a community-based agency (n = 4). The programs' focus on the social determinants of health, and their provision of primary, prenatal, perinatal and mental health care services is essential; similarly, on-site substance use and trauma/violence related services is pivotal. Further, programs' support in relation to women's child welfare issues promotes collaboration, common understanding of expectations, and helps to prevent child/infant removals. Conclusions The programs involved in the Co-Creating Evidence study have impressively blended social and primary care and prenatal care. Their success in respectfully and flexibly responding to women's diverse needs, interests and readiness, within a community-based, wraparound service delivery model paves the way for others offering pre- and postnatal programming.